Rehabilitation of Brougham Castle Bridge, UK. Issue 1 (30th October 2018) - Wiggins, David; Mudd, Kiera; Healey, Matthew
Abstract : Brougham Castle Bridge is a three-span masonry arch highway bridge that has suffered significant scour damage to foundations and substructure with referred damage through the superstructure. This paper presents an engineer's account of the appraisal, investigation, assessment of structural action and the design and execution of repairs for stabilising the structure. The analytical tool employed to interpret the flow of force was a thrust-line graphical equilibrium analysis. It will be demonstrated that this analytical approach accords with the observed structural pathology, thus giving a clear understanding as to where the loads are going, that they may be effectively grappled with. Through thrust-line analysis, continued stability could be demonstrated despite substantial changes in the foundation conditions. It seems fitting that this efficient, robust and confidence-building tool is the same used by the engineers who originally designed many of these bridges. Using this 'historical approach', a successful intervention was executed; initially emergency stabilisation work to save the bridge from collapse and latterly permanent rehabilitation works to bring the bridge back into service in advance of the upcoming winter floods.